Sodium Hypochlorite and Chlorhexidine Downregulate MMP Expression on Radicular Dentin - Retana-Lobo, Cristina; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP]; Mendes De Souza, Beatriz D.; Reyes-Carmona, Jessie (Karger Publishers, 2021)
Objective: Matrix metalloproteinases (MMPs) are present in radicular dentin and can convert structural matrix proteins into signaling molecules; thus, these enzymes play an essential role in dentin biomineralization and tissue regeneration therapies. Their expression on radicular dentin may be affected by the irrigation solutions used during root canal treatments. This study aimed to evaluate the effects of the most common irrigants on radicular dentin MMP expression. Materials and Methods: The experimental solutions were distilled water (control), 5% sodium hypochlorite (NaOCl), 18% ethylenediaminetetraacetic acid (EDTA), and 2% chlorhexidine (CHX). Samples were prepared from extracted human teeth. For zymography analysis, root sections were powderized, and dentin proteins were extracted to observe gelatinolytic activity. Root dentin slices were treated with the experimental solutions for immunohistochemical analysis using anti-MMP-2 and anti-MMP-9 antibodies. ANOVA and the Tukey test were performed. Results: Zymograms revealed the presence of MMP-2, MMP-8, and MMP-20 in the control group and the EDTA-treated group. Immunohistochemistry confirmed the presence of MMP-2 and MMP-9 mainly associated with the dentinal tubule lumens and occasionally with intertubular dentin. NaOCl- and CHX-treated groups showed lower expression of MMPs than the control group. Immuno-staining for both proteinases in the EDTA-treated group showed higher expression compared to the other experimental groups. Conclusion: Our results showed that most common irrigants affect MMP expression on radicular dentin. Treatment with NaOCl and chlorhexidine resulted in lower expression of MMPs, while EDTA increased their expression in root canal dentin.
Keywords: Endodontics; Matrix metalloproteinases; Root canal irrigants